Guidance Model to Proactive Coping Skills - Asada Ploysopon; Ratanaporn Loungkeaw; Nongyao Nuchanart (Universitas Muhammadiyah Yogyakarta, 2023)
This study aims to (1) study the current state and needs of a guidance model that promotes proactive coping skills; (2) develop a guidance model to strengthen proactive coping skills; and (3) study the effect of using the development of a guidance model to enhance proactive coping skills. The research method was Research and Development (RD). The development model used is ADDIE. The sample used was 250 undergraduate students at Suan Dusit University by stratified sampling. The instruments used in this study were the current conditions and needs questionnaire, the structured interview form for studying current conditions and needs, the proactive coping strategies scale, and the opinion exam form. Analysis techniques included the Priority Needs Index (PNI Modified) and an independent t-test. This study concludes that (1) the highest priority needs among counseling services, administrative structure, activities that respond to student needs, activities to support and strengthen coping skills, and promoting positive attitudes towards self and the university are ranked in that order; (2) a guidance model for enhancing proactive coping skills consists of five components, namely Administrative, Staff, Activity, Deming Cycle, and Assessment; and (3) the Asada model is effective in reinforcing proactive coping skills.